An in-depth investigation on the formation of nanoporous silica microspheres in diluted dodecylamine solutions. Issue 7 (2nd May 2016) - Liu, Shiquan; Zhao, Hui
Abstract: The morphology and textural characteristics of silica products formed via the hydrolysis and condensation of tetraethyl orthosilicate in increasing diluted dodecylamine solutions have been investigated. The results show that the pH values of the synthesis media increase with the initial additions of water. The formation of silica speeds up as the solution is diluted. As a result, microporous silica microspheres with increasing surface areas, pore volumes, pore and particle sizes are formed by a monomer addition mechanism. Further increases in the amount of water result in the decrease of the concentrations of OH − . Consequently, the formed silica seeds become less active and the diffusion of silica species is accelerated. The monomer addition process thus becomes difficult. The self-nucleation of silica species leads to the formation of large quantities of primary silica nano particles. In order to minimise the internal energy of the reaction system, the nanoparticles aggregate to form micrometre-sized silica microspheres with a relatively loose structure. The synthesised microspheres can be used in the removal of organic pollutants in water. It is shown that the nanoporous silica microspheres formed by the aggregation mechanism have a faster dye adsorption rate and a higher adsorption capacity than those formed by the monomer addition mechanism.